Impaired human responses to tetanus toxoid in vitamin A-deficient SCID mice reconstituted with human peripheral blood lymphocytes. - Molrine, D C (1995)
Vitamin A deficiency is associated with increased childhood morbidity and mortality from respiratory and diarrheal diseases. In order to evaluate the effect of vitamin A on human antibody responses, we developed a vitamin A-deficient severe combined immunodeficient (SCID) mouse model. Vitamin A-deficient mice were produced by depriving them of vitamin A at day 7 of gestation. Mice were reconstituted with human peripheral blood lymphocytes (huPBL) from tetanus toxoid immune donors at 6 weeks of age and immunized with tetanus toxoid at 6 and 8 weeks of age. Secondary human antibody responses were determined 10 days later. The geometric mean human anti-tetanus toxoid immunoglobulin G concentrations were 3.75 micrograms/ml for the deficient mice and 148 micrograms/ml for controls (P = 0.0005). Vitamin A-deficient mice had only a 2.9-fold increase in human anti-tetanus toxoid antibody compared with a 74-fold increase in controls (P < 0.01). Supplementation with vitamin A prior to reconstitution restored human antibody responses to normal. These data suggest that vitamin A deficiency impairs human antibody responses. We speculate that impaired responses could increase susceptibility to certain infections. Furthermore, we propose that effects of other nutritional deficiencies on the human immune system could be evaluated in the SCID-huPBL model.